Causal Relationship Model of Transformational Leadership, Learning Organization and Quality of Work Life Influencing Patient Unit Performance in General Hospitals under the Ministry of Public Health - มีหาญพงษ์ ปราณี; วงษ์ขมทอง จันทร์จิรา; บุญศิลป์ สุนีย์รัตน์; ศรีทุมมา เนตรชนก (Nursing Journal of The Ministry of Public Health, 2019)
The purposes of this correlational research were to identify and test a causal relationship model of transformational leadership learning organization, quality of work life and patient unit performance. The multi-stage sampling technique was used to include 386 nurses at eighty-three general hospitals under the Ministry of Public Health, Thailand. They were asked to answer five sets of questionnaires: 1) Personal Data Form, 2) Transformational Leadership Questionnaire, 3) Learning Organization Questionnaire, 4) Quality of Work Life Questionnaire, and 5) Patient Unit Performance Questionnaire. The reliability of each questionnaire had a Cronbach’s alpha Coefficient of .98, .98, .97 and .91, respectively. Data were analyzed using the statistical data analysis program for Structural Equation Modeling: SEM. The findings of this study revealed patient unit performance was at the high level ( =3.61, SD=.41). Transformational leadership of head nurse had positive direct effects on learning organization and quality of work life (ß=.59, ß=.55 p<.001), respectively. Transformational leadership of the head nurse also had an indirect effect on patient unit performance through learning organization (ß=.09, p<.001), it also had an indirect effect on patient unit performance through quality of work life (ß=.35, p<.001). Learning organization had positive direct effects on patient unit performance (ß=.16, p<.001), and quality of work life had positive direct effects on patient unit performance (ß=.64, p<.001). The model accounted for 59 % of the variance in Patient Unit Performance and a substantial proportion of the variance of the mediating variables.